Future proofing teachers in inclusive education through social and emotional competencies and instruction - Enorio, Mary Lovelenn L. (Laguna : National University, 2024)
This study focused on future proofing teachers in an Inclusive Education through SEC and Instruction.
Chapter 1. Introduction -- Chapter 2. Review of Related Literature and studies -- Chapter 3. Methodology -- Chapter 4. Results and Discussion -- Chapter 5. Summary, Conclusion and recommendation -- References.
Quantitative with an embedded qualitative to support quantitative result.
Includes bibliographical references.
Keywords: FUTURE PROOFING; INCLUSIVE EDUCATION